The Role Of The Chef De Partie In Support Operations In The Pastry Section Of Hotel Novotel Semarang - Prita Filadelfia; Dedi Joko Purnomo (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
Prita Filadelfia. C13.2019.00239. 2023. The Role of a Chef de Partie in Supporting Operations in the Pastry Department of Novotel Hotel Semarang. Bachelor of Applied Science in Hospitality Management, Faculty of Cultural Studies, Dian Nuswantoro University.This final project aims to explain the role of a Chef de Partie, especially how the Pastry Department supports the operations. A Chef de Partie has the duty and responsibilities to manage the team. Lack of supervision from a leader makes an operation not run well, so guest complaints can occur. This research used qualitative descriptive methodology for data collection. The data was collected with interviews, observations, and documentation to obtain accurate data regarding the role of a Chef de Partie in the operations of the pastry section. The research results obtained by researchers are that a Chef de Partie has a very important role in leading his team so as to minimize a problem and be able to overcome problems at the internal and external levels, but if the duties and responsibilities are not carried out properly then it can lead to unsatisfactory product results and guest complaints. The role of a Chef de Partie is very influential in the operations of the pastry section in order to improve the image of a hotel and guest satisfaction.